Do disturbance-sensitive and habitat-specialized species have a smaller range size? Evidence for a set of common mammals at regional scale. Issue 5 (3rd September 2019) - Battisti, Corrado; Fanelli, Giuliano; Amori, Giovanni; Luiselli, Luca; Capizzi, Dario
Abstract : Disturbance-sensitivity and habitat generalism are two important eco-behavioural traits of species. In this paper, we calculated these traits for a set of 21 common mammal species using two proxies (HSrescaled for disturbance-sensitivity, and HHi, for habitat generalism) here obtained synthesizing the numbers and frequency of differently disturbed habitats where a species occurs. Then, we correlated them to their regional range size in Latium (Central Italy). HSrescaled and HHi resulted correlated between them. Moreover both these metrics resulted (or tend to be) positively correlated with the regional range size of species. A GLM model showed that disturbance-sensitivity of the species is more explicative to predict regional range size when compared to generalism. Although with some limitations, this data deserves attention for its implications both in basic and applied ecology. Indeed, (i) our data corroborate the strictly relationship between niche-width and geographic distribution of species at regional scale, and (ii) we obtained eco-behavioural evidence useful for conservation strategies: indeed many of species yet included in list of disturbance-sensitive taxa at landscape scale can be confirmed as indicators of disturbed habitat types.